2023
DOI: 10.1073/pnas.2217396120
|View full text |Cite
|
Sign up to set email alerts
|

Octopamine metabolically reprograms astrocytes to confer neuroprotection against α-synuclein

Abstract: Octopamine is a well-established invertebrate neurotransmitter involved in fight or flight responses. In mammals, its function was replaced by epinephrine. Nevertheless, it is present at trace amounts and can modulate the release of monoamine neurotransmitters by a yet unidentified mechanism. Here, through a multidisciplinary approach utilizing in vitro and in vivo models of α-synucleinopathy, we uncovered an unprecedented role for octopamine in driving the conversion from toxic to neuroprotective astrocytes i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 63 publications
0
4
0
Order By: Relevance
“…In an unbiased transcriptional approach using RNA sequencing (RNA-Seq), we previously found that one of the most prominent upregulated genes in α-syn neuronal cultures treated with neuroprotective doses of FK506 was the IGF-1 signaling pathway ( Shum et al, 2023 ). IGF-1 signaling has been shown to be neuroprotective, partially due to its role in inhibiting neuroinflammation ( Sukhanov et al, 2007 ; Park et al, 2011 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In an unbiased transcriptional approach using RNA sequencing (RNA-Seq), we previously found that one of the most prominent upregulated genes in α-syn neuronal cultures treated with neuroprotective doses of FK506 was the IGF-1 signaling pathway ( Shum et al, 2023 ). IGF-1 signaling has been shown to be neuroprotective, partially due to its role in inhibiting neuroinflammation ( Sukhanov et al, 2007 ; Park et al, 2011 ).…”
Section: Resultsmentioning
confidence: 99%
“…Based on the previous work through candidate and unbiased approaches ( Caraveo et al, 2014 ; Shum et al, 2023 ), we have now identified two plausible biomarkers responsive to the neuroprotective properties of FK506 in vivo : IL-2 and IGF-1. IL-2 expression is primarily regulated by NFAT, a bona fide calcineurin substrate ( Serfling et al, 2000 ; Bueno et al, 2002 ; Hogan et al, 2003 ; Macian, 2005 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations